Investigating the effect of total assets, financing, and third-party funds on Islamic Banking Revenue in Indonesia - Rani Salamah Marinda; Imam Asngari; Mukhlis Mukhlis (Department of Development Economics, Universitas Sriwijaya, 2020)
This study investigates the influence of total assets, total financing, and third-party funds on the revenue of Islamic banking in Indonesia. Data used are secondary data during the period 2005-2018 sourced from the Financial Services Authority (OJK). The study analysis used a quantitative approach by applying the multiple regression model estimated by OLS. The findings of the study indicated that total assets and third-party funds has a positive and significant effect, while the financing has a negative and significant effect on Islamic banking revenue in Indonesia during the analysis period